Introduction to biological physics for the health and life sciences - Franklin, Kirsten ([Chichester, U. K.] : John Wiley & Sons, 2010)
'This books aims to demystify fundamental biophysics for students in the health and biosciences required to study physics and to understand the mechanistic behaviour of biosystems. The text is well supplemented by worked conceptual examples that will constitute the main source for the students, whilst combining conceptual examples and practice problems with more quantitative examples and recent technological advances'--
Includes bibliographical references and index.
Keywords: Biophysics -- Textbooks; Physics -- Textbooks; Medical physics -- Textbooks